The Role of Digital-Based Entrepreneurship Education in the Success of Community Empowerment Programs for Subsistence UMKM Groups within the Creative Indonesian Women's Community in Samarinda City: Peran Pendidikan Kewirausahaan Berbasis Digital Dalam Keberhasilan Program Pemberdayaan Masyarakat Kelompok UMKM Subsisten Pada Komunitas Perempuan Kreatif Indonesia di Kota Samarinda - Salim, Rio Gunawan; Iip Saripah; Kamil, Mustofa; Yunus Lutfiansyah, Dadang; Farmawati, Windie Karina (Borneo Educational Journal (Borju), 2026)
Amidst the rapid growth of digital literacy, subsistence UMKM are a low-income group, particularly female heads of households who are the backbone of their families, facing the dual challenges of limited access to resources and digital literacy gaps. The government plays an active role in community empowerment programs through training in general business development. Therefore, community empowerment through digital-based entrepreneurship education addresses these challenges by opening mindsets, connecting ideas, skills, and market access through digital technology, and promoting cross-sector collaboration in a mutually reinforcing ecosystem. This study aims to determine the role of digital-based entrepreneurship education in the success of such community empowerment programs. This research collaborates with the Women's Empowerment Agency (DP2PA) in collaboration with the Indonesian Creative Women's Community and academics from the UMKM Entrepreneurship Institute of Widya Gama Mahakam University in Samarinda in an empowerment program through non-formal entrepreneurship education at women's business schools. This research is a qualitative descriptive study, with data obtained through interviews and observations, using instruments in the form of interview guides and observation guides. There were 15 participants consisting of organizers, mentors, facilitators, and business school participants. The data analysis process was applied inductively by referring to Miles and Huberman's interactive model, which includes five stages, namely data collection, data presentation, data reduction, conclusion drawing, and verification. The results of the study show that the success of the empowerment program requires the role of entrepreneurship education in encouraging an entrepreneurial attitude, the ability to identify and create business opportunities, and the ability to integrate digital technical skills and strengthen the entrepreneurial mindset. In practical terms, this study concludes that amid digital disruption, digital-based entrepreneurship education, mentoring, and community become the main catalysts for the transition of subsistence UMKM to sustainable businesses